Thermodynamic and microstructural study of Ti(2)AlNb oxides at 800 °C - Xiang, J. M. (Sci Rep, 2018)
The high-temperature structural applications of Ti(2)AlNb-based alloys, such as in jet engines and gas turbines, inevitably require oxidation resistance. The objective of this study is to seek fundamental insight into the oxidation behavior of a Ti(2)AlNb-based alloy via detailed microstructural characterization of oxide scale and scale/substrate interface after oxidation at 800 °C using X-ray diffraction (XRD), scanning electron microscopy (SEM), electron probe microanalysis (EPMA), and transmission electron microscopy (TEM). The oxide scale exhibits a complex multi-layered structure consisting of (Al,Nb)-rich mixed oxide layer (I)/mixed oxide layer (II)/oxygen-rich layer (III)/substrate from the outside to inside, where the substrate is mainly composed of B2 and O-Ti(2)AlNb phases. High-resolution TEM examinations along with high-angle annular dark-field (HAADF) imaging reveal: (1) the co-existence of two types (α and δ) of Al(2)O(3) oxides in the outer scale, (2) the presence of metastable oxide products of TiO and Nb(2)O(5), (3) an amorphous region near the scale/substrate interface including the formation of AlNb(2), and (4) O-Ti(2)AlNb phase oxidized to form Nb(2)O(5), TiO(2) and Al(2)O(3).